Desenvolvimento in vitro de copo-de-leite: efeito das concentrações de sacarose e de ácido giberélico - Oliveira Ribeiro, Marcia de Nazare; Pasqual, Moacir; Villa, Fabiola; Cavallari, Ludmilla de Lima [UNESP] (Universidade Estadual de Londrina (UEL), 2009)
Calla lily (Zantedeschia aethiopica) is appreciated as cut flower and for the composition of gardens. However, many pathogens affect this species. By the traditional method of propagation, some units of new seedlings can only be produced annually. Tissue culture allows fast large-scale clonal propagation and provides healthy uniform plants. During the in vitro process, type and concentration of growth regulator could affect the growth of seedlings. Thus, the aim of this work was to determine sucrose and GA(3) concentrations to increase the efficiency of the in vitro multiplication of calla lily. After 60 days, the length of the above ground part and the roots, the number of sprouts, roots and leaves, above ground part and root fresh weight of seedlings were evaluated. The experimental design was entirely randomized with four replications. It was necessary the addition of 60.5 g L-1 sucrose associated to 5 mg L-1 GA(3) to obtain hight sprouts number. For higher length of the above ground part the addition of 45.3 g L-1 sucrose and 10 mg L-1 GA(3) was enough. Better results in the root length and number of roots were observed only in the sucrose presence, in concentrations in the range of 51.13 - 56.5 g L-1.
In vitro development of calla lily: effect of sucrose and gibberellic acid concentrations
Keywords: Tissue culture; carbohydrate; growth regulator